The Influence of Work Discipline, Coordination, and Communication on Employee Performance at the Curug Flight Facility Calibration Center In Tangerang Indonesia - Ary Priyambodo; Agus Nugraha (Yayasan Ilomata, 2019)
The purpose of this study was to determine the effect of work discipline, coordination, and communication on employee performance. The theory used in this study refers to the opinions of Hasibuan, Wexley and Yulk and difficult. There is an influence of work discipline, coordination, and communication on employee performance. The research method used is a quantitative method through questionnaires, with a population of 188 and the sample is 65 respondents, based on the Slovin formula. Based on the results of research using path analysis with the help of SPSS version 24 shows that there is no significant influence there is a significant influence on work discipline, the joint coordination and communication on employee performance at Curug Flight Facility Calibration Center of Tangerang Indonesia at 71.6% and the remaining 28.4% which affect the performance of employees but not examined.